Cyberbullying Menurunkan Dua Kali Motivasi Belajar Siswa - Dian Sari (SEHATI: Jurnal Kesehatan, 2024)
Motivation to learn is a critical factor for achieving academic success. Low motivation can lead to serious issues such as school dropout and involvement in criminal activities. This study aims to explore the factors that influence student learning motivation. A cross-sectional design was employed, involving 198 junior and senior high school students selected through convenience sampling. The study was conducted in April and May 2024. Data were collected via questionnaires distributed through the g-form platform and shared via social media. Bivariate analysis was performed using chi-square and t-tests. Meanwhile a multivariable logistic regression was used to examine the association of cyberbullying and other factors to learning motivation. Results indicated that cyberbullying (p = 0.013), school bullying (p = 0.032), and school type (p = 0.041) significantly influenced student learning motivation (p less than 0.05). Our multivariate analysis revealed that incidents of cyberbullying were the most influential factor, reducing student learning motivation by a factor of two (AOR = 2.10; 95% CI = 1.16-3.82). These findings highlight the need for preventive efforts against cyberbullying through educational programs and campaigns promoting the responsible use of digital devices, as well as increased parental supervision.